FORMATIVE QUIZZES TO IMPROVE INSTRUCTION, STUDENT’S PARTICIPATION AND UNDERSTANDING IN ACADEMIC WRITING - Saidah, U. H. (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
A combination of presentation and discussion as an instruction method is excellent per se. However if it is implemented in a classroom unceasingly without any other instruction variations, it might cause discouragement of students in their learning. To vary, there are a lot of instruction methods available to improve instruction as well as students’ participation and understanding, one of which is formative quiz. A formative quiz is an informal test given to students as an assessment conducted continuously aimed at adjusting instructional practices in order to improve students’ learning. In implementing formative quizzes as an instruction method, an investigation is conducted using classroom action research design operating two cycles. The first cycle is to measure the lecturer’s instruction, and the second cycle is to measure the students’ participation and understanding. Conclusively it is found out that formative quizzes have improved lecturer’s instruction, students’ participation and understanding in academic writing course.